Dissimilatory nitrate reduction processes in surface sediments of shrimp ponds during the culture period - Sun, Dongyao; Huang, Jiafang; Luo, Min; Chen, Cheng; Lan, Xue; Hu, Weifang (Frontiers in Marine Science, 2022)
Intensive aquaculture in estuaries and coasts has resulted in several ecological and environmental problems. Among various nitrogen transformation pathway, dissimilatory nitrate (NO3-) reduction is considered to be highly important in regulating reactive nitrogen. However, there are relatively few studies on the processes and contribution of NOx- reduction in sediment during the shrimp pond culture period. Three sediment NO3- reduction processes, denitrification (DNF), anaerobic ammonium oxidation (ANA), and dissimilatory NO3- reduction to ammonium (DNRA), were surveyed in eight shrimp ponds across three subtropical estuaries using 15N isotope tracing experiments. The rates of DNF, ANA and DNRA ranged from 2.87–18.11, 0.10–1.92, and 0.21–1.25 nmol N g -1 h -1, respectively. DNF was responsible for 64.2–91.6% of the total NO3- reduction. Regarding environmental factors, C and N substrates, as well as salinity, significantly affected NO3- reduction. In general, the N losses were approximately 32.43–131.64 g N m-2 yr-1 for DNF and 2.38–15.85 g N m-2 yr-1 for ANA in this study, indicating that coastal reclamation is a nonnegligible way to remove nitrogen. Our results provide a scientific foundation for understanding the mechanism of nitrogen cycling in the artificial aquatic environment of shrimp ponds.